Literature review: effects of high-intensity intervallic training on autonomic balance and oxygen consumption kinetics in obese subjects. (Revista horizonte, 2016)
Obesity is a prevalent disease in Chile and the world, associated with an imbalance between expenditure and energy consumption. This condition is associated with a decreased functional capacity and decreased oxygen consumption kinetics. Besides, the increase in adipose tissue produces an alteration of the chronic regulation in the autonomic nervous system, both at rest and during exercise, which involves an altered response of the parasympathetic activity. Objective: to describe the mechanisms that show the relationship between vagal activity and kinetics of oxygen consumption in obese subjects as well as to clarify the impact of high-intensity intervallic training on these two parameters. Methods: A search was conducted in PubMed, MEDLINE and CINAHL database, which included controlled clinical trials, meta-analyzes and reviews for their inclusion in the review work. Results: there is little scientific evidence to explain the effect of the autonomic imbalance on the kinetics of oxygen consumption, as well as the potential impact or the subsequent recovery of postintervention kinetics with high intensity intervallic training. Conclusion: There is not enough evidence describing the effect of the autonomic imbalance in the kinetics of oxygen consumption, although trends for improvements were observed in both parameters after a high-intensity intervallic training in obese subjects.